PENERAPAN SANKSI TERHADAP ANAK SEBAGAI PELAKU TINDAK PIDANA INSES - Nisrina Tsabita Irbah (2021)
This study aims to examine how to apply appropriate sanctions in cases when a child becomes the perpetrator of incest. This is because there is no legal rule regarding incest in Indonesia. The rules that apply in cases of incest are rules regarding rape and sexual immorality. The imposition of sanctions given to children who are perpetrators must be based on Restorative Justice and in accordance with Law No. 35 of 2014 concerning Amendments to Law No. 23 of 2002 concerning Child Protection. The sanctions given to children can be reviewed from Law No. 11 of 2012 concerning the Judicial System. Child Criminal. In this research, the method used is the normative juridical method using the Law approach. The criminal sanctions that can be applied to children as perpetrators of incest must be further reviewed because the child perpetrators may have to receive rehabilitation.